Mathematical Models of Cobalt and Iron Ions Catalyzed Microwave Bacterial Deactivation - Arthur L. Williams (International Journal of Environmental Research and Public Health, 2007)
Time differences for Enterococcus faecalis, Staphylococcus aureus, and Escherichia coli survival during microwave irradiation (power 130 W) in the presence of aqueous cobalt and iron ions were investigated. Measured dependencies had "bell" shape forms with maximum bacterial viability between 1 - 2 min becoming insignificant at 3 minutes. The deactivation time for E. faecalis, S. aureus and E.coli in the presence of metal ions were smaller compared to a water control (4 -5 min). Although various sensitivities to the metal ions were observed, S. aureus and E. coli and were the most sensitive for cobalt and iron, respectively. The rapid reduction of viable bacteria during microwave treatment in the presence of metal ions could be explained by increased metal ion penetration into bacteria. Additionally, microwave irradiation may have increased the kinetic energy of the metal ions resulting in lower survival rates. The proposed mathematical model for microwave heating took into account the "growth" and "death" factors of the bacteria, forming second degree polynomial functions. Good relationships were found between the proposed mathematical models and the experimental data for bacterial deactivation (coefficient of correlation 0.91 - 0.99).